Microplastics contamination in food and beverages: Direct exposure to humans - Jin, Mengke; Wang, Xue; Ren, Tao; Wang, Jian; Shan, Jiajia (Journal of food science, 2021)
Since microplastics (MPs) bring the potential risks to human health when plastics are ingested, more needs to be known about the presence and abundance of human ingestion of MPs. To address these issues, we reviewed 108 publications in Web of Science concerning abundances, sources, and analytical methods of MPs in human daily intake including fish, salt, drinking water, beverages, package food, and other food. The results demonstrate that aquatic food products (fish and bivalves) present a wide range of 0–10.5 items/g for bivalves and 0–20 items/individual for fish. Salt data in literatures present a concentration of 0–13,629 particles/kg. Drinking water is also a pathway of MPs exposure to human, presenting a concentration range from 0 to 61 particles/L for tap water and 0 to 6292 MPs/L for bottled water. Besides, MPs have been found in beverages, package food, sugar, honey, vegetables, and fruits. Therefore, human intake of MPs via ingestion is a nonnegligible exposure route.